Transformasi Indeks Pembangunan Manusia di Nusa Tenggara Barat: Trend Analysis and Challenges 2019-2023 - Utami, Karina Juniarti (Kainawa: Jurnal Pembangunan dan Budaya, 2024)
The Human Development Index (HDI) is an important indicator for assessing the quality of development in a region. West Nusa Tenggara (NTB) faces challenges in improving its HDI, which is influenced by various factors such as education, health, and the economy. Despite efforts to enhance the HDI, disparities among regions in NTB indicate that not all areas are experiencing the same progress. This raises questions about the factors influencing these differences. Previous research has not comprehensively analyzed the interconnections among human development indicators and their impact on the HDI in NTB. This study aims to analyze the dynamics of the HDI in NTB from 2019 to 2023, focusing on the factors affecting growth and regional disparities. The methodology employed in this research is qualitative analysis with a comprehensive approach, including statistical analysis to identify patterns and relationships among indicators. The results show that Central Lombok Regency and Mataram City have better HDI achievements compared to other regions, with education and life expectancy as the main driving factors. These findings indicate the need for more focused and evidence-based development strategies to address disparities and improve the quality of life for the people in NTB. The study concludes that a holistic and collaborative approach is necessary to optimize regional potential. Recommendations include allocating budgets that are more responsive to local needs and improving the quality of education and health services.